2008
DOI: 10.1002/cmdc.200700208
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Cytidine Derivatives that Inhibit the Kinase IspE of the Non‐Mevalonate Pathway for Isoprenoid Biosynthesis

Abstract: The enzymes of the non-mevalonate pathway for isoprenoid biosynthesis are attractive targets for the development of novel drugs against malaria and tuberculosis. This pathway is used exclusively by the corresponding pathogens, but not by humans. A series of water-soluble, cytidine-based inhibitors that were originally designed for the fourth enzyme in the pathway, IspD, were shown to inhibit the subsequent enzyme, the kinase IspE (from Escherichia coli). The binding mode of the inhibitors was verified by co-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
40
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 59 publications
1
40
0
Order By: Relevance
“…Sequence-structure comparisons revealed that the active site and ligand interactions are highly conserved for YchB and that A. aeolicus YchB represents a suitable model for the human pathogen M. tuberculosis . A. aeolicus IspE has proved invaluable for providing structural information in the structure-based design approach for the generation of IspE inhibitors for organisms such as Plasmodium falciparum and M. tuberculosis (Crane et al, 2008;Hirsch et al, 2008). Co-crystal structure analysis (Crane et al, 2008;Hirsch et al, 2008) and structure-activity relationships (SARs) of A. aeolicus IspE have validated the binding mode of several new inhibitors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sequence-structure comparisons revealed that the active site and ligand interactions are highly conserved for YchB and that A. aeolicus YchB represents a suitable model for the human pathogen M. tuberculosis . A. aeolicus IspE has proved invaluable for providing structural information in the structure-based design approach for the generation of IspE inhibitors for organisms such as Plasmodium falciparum and M. tuberculosis (Crane et al, 2008;Hirsch et al, 2008). Co-crystal structure analysis (Crane et al, 2008;Hirsch et al, 2008) and structure-activity relationships (SARs) of A. aeolicus IspE have validated the binding mode of several new inhibitors.…”
mentioning
confidence: 99%
“…A. aeolicus IspE has proved invaluable for providing structural information in the structure-based design approach for the generation of IspE inhibitors for organisms such as Plasmodium falciparum and M. tuberculosis (Crane et al, 2008;Hirsch et al, 2008). Co-crystal structure analysis (Crane et al, 2008;Hirsch et al, 2008) and structure-activity relationships (SARs) of A. aeolicus IspE have validated the binding mode of several new inhibitors. Buetow et al (2007) determined the crystal structure of M. smegmatis YghB, which has a high degree of similarity to YghB of M. tuberculosis.…”
mentioning
confidence: 99%
“…At a time when there is an urgent need for new antimicrobial agents against resistant organisms, some suggested that it might be useful to identify new structural classes heretofore not observed [26]. Despite attempts to design specific CDP-ME kinase inhibitors by synthesizing derivatives of cytidine/cytosine [2729], there has been no documented experimental, random HTS of inhibitors for E. coli or other bacterial CDP-ME kinases. Although these proof-of-principle approaches are valid, the identified inhibitors shared closely similar chemotypes and in some cases, IC 50 values of mM (millimolar) range [27].…”
Section: Resultsmentioning
confidence: 99%
“…Despite attempts to design specific CDP-ME kinase inhibitors by synthesizing derivatives of cytidine/cytosine [2729], there has been no documented experimental, random HTS of inhibitors for E. coli or other bacterial CDP-ME kinases. Although these proof-of-principle approaches are valid, the identified inhibitors shared closely similar chemotypes and in some cases, IC 50 values of mM (millimolar) range [27]. In this study, we took two different approaches to expand the repertoire and diversity of the bacterial CDP-ME kinase inhibitors.…”
Section: Resultsmentioning
confidence: 99%
“…The structural and mechanistic information summarized above served as the basis for the rational design of inhibitors for IspE and IspF protein [83][84][85][86][87][88][89][90]. In both cases, the cytosine motif present in the substrate and/or product served as the basic template.…”
Section: -C-methylerythritol 4-phosphate Is Converted Into a Cyclic mentioning
confidence: 99%